“O‘ZBEKISTON SANOAT TARMOQLARIDA INNOVATSION RIVOJLANISHNING IQTISODIY SAMARADORLIGI” (JIZZAX VILOYATI MISOLIDA) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2025)
This article analyzes the current development processes of industrial sectors of Uzbekistan, the increase in regional industrial potential, the economic efficiency of introducing innovative technologies and developing investment activities. The results of the reforms implemented in the country within the framework of the innovative development strategy for 2022-2026, new trends in the field of technoparks, innovation zones and renewable energy sources are analyzed on a scientific basis.